2022
DOI: 10.3389/fpsyg.2022.791803
|View full text |Cite
|
Sign up to set email alerts
|

How and When Daily Abusive Supervision Affects Daily Organizational Citizenship Behavior for the Environment

Abstract: Organizational environmental sustainability depends primarily on employees’ organizational citizenship behavior for the environment (OCBE), and leadership plays an important role in improving and inhibiting employees’ OCBE. The purpose of the present study is to examine the mediation process by which abusive supervision affects employees’ OCBE through a daily diary study and to explore the boundary conditions of the relationship between daily moral disengagement and daily OCBE. We collected data from 112 Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…A literature review showed that abusive supervision was negatively associated with subordinates' attitudes, behaviours, relationships and overall well-being [8]. For example, abusive supervision had a negative effect on organizational citizenship behaviour [9], organizational commitment [10] and performance [11], increased emotional exhaustion [12] and turnover intention [13]. Abusive supervision is a widespread but intractable social issue that may exist beyond formal employment relationships [14].…”
Section: Abusive Supervisionmentioning
confidence: 99%
“…A literature review showed that abusive supervision was negatively associated with subordinates' attitudes, behaviours, relationships and overall well-being [8]. For example, abusive supervision had a negative effect on organizational citizenship behaviour [9], organizational commitment [10] and performance [11], increased emotional exhaustion [12] and turnover intention [13]. Abusive supervision is a widespread but intractable social issue that may exist beyond formal employment relationships [14].…”
Section: Abusive Supervisionmentioning
confidence: 99%
“…For instance, abusive supervision decreased organizational citizenship behavior (H. Q. Wang & Xiao, 2022) and organizational commitment (Y. T.…”
Section: Abusive Supervisionmentioning
confidence: 99%
“…Internally, OCB allows organizations to operate more effectively, thereby enhancing organizational performance ( Williams and Polito, 2022 ). Externally, OCB improves service quality and customer satisfaction ( Wang and Xiao, 2022 ). According to Azizaha et al (2020) and Desky et al (2020) , OCB is a profound contribution that is beyond what is required by one’s job at the workplace and is rewarded by the organization based on the performed tasks.…”
Section: Conceptual Frameworkmentioning
confidence: 99%